2006
DOI: 10.1242/jeb.02456
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory behavioural assay of insect magnetoreception:magnetosensitivity of Periplaneta americana

Abstract: SUMMARY A relatively simple all-laboratory behavioural assay of insect magnetoreception has been developed. We found non-conditioned reactions of American cockroach to the periodical shifts of the geomagnetic field. The movement activity of animals individually placed into Petri dishes was scored as a number of body turns. Test groups were exposed to a 90-min interval with the horizontal component of the geomagnetic field periodically rotated by 60° back and forth with 5 min periodicity. The num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 28 publications
4
41
0
Order By: Relevance
“…Here, we have taken advantage of an assay enabling us to test directional magnetic sensitivity in insects at naturally occurring GMF intensities (30) and functionally confirmed that mammalianlike Cry2 is necessary for sensing the directional component of MFs of natural intensities by two different species of cockroaches.…”
Section: Significancementioning
confidence: 62%
“…Here, we have taken advantage of an assay enabling us to test directional magnetic sensitivity in insects at naturally occurring GMF intensities (30) and functionally confirmed that mammalianlike Cry2 is necessary for sensing the directional component of MFs of natural intensities by two different species of cockroaches.…”
Section: Significancementioning
confidence: 62%
“…The assay testing magnetic susceptibility of cockroaches (for details, see Vácha, 2006) is based on comparing activity (the number of body position changes larger than 15deg.) in (and 45min after) the interval in which the position of the magnetic North is rotated by 60deg.…”
Section: Methodsmentioning
confidence: 99%
“…As described in Vácha (Vácha, 2006), Wilcoxon dependent test was used to compare the frequency of body orientation changes in CDE interval (the North position rotations and 45min after) versus the ABF interval (the North position is stable).…”
Section: Statistical Processingmentioning
confidence: 99%
See 2 more Smart Citations